Pengaruh Praktik Kerja Industri Dan Kompetensi Kejuruan Terhadap Kesiapan Kerja Dengan Mediasi Efikasi Diri Pada Siswa Kelas XII Kompetensi Keahlian Akuntansi Di SMK Negeri Jakarta Selatan - Nadya Pitaloka; Ati Sumiati; Dwi Kismayanti Respati (Fakultas Ekonomi Universitas Negeri Jakarta, 2022)
This research was conducted with the aim of knowing the effect of industrial work practice, vocational competence, and self-efficacy on job readiness and the effect of industrial work practice and vocational competence on job readiness through self-efficacy in Class XII students of Accounting Skills Competence at the South Jakarta State Vocational High School. This research is a quantitative research with survey method. The population used is 174 with a sample of 114 students. The data analysis technique used is influence analysis or path analysis through the SPSS 24 program. The research results obtained, namely there is a positive and significant influence on industrial work practices, vocational competence, and self-efficacy on job readiness partially, and there is a positive and significant influence on practice industrial work on job readiness through self-efficacy and vocational competence on job readiness through self-efficacy.